y=x*(x-1)

Simple and best practice solution for y=x*(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=x*(x-1) equation:


Simplifying
y = x(x + -1)

Reorder the terms:
y = x(-1 + x)
y = (-1 * x + x * x)
y = (-1x + x2)

Solving
y = -1x + x2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -1x + x2

See similar equations:

| 1+5x=-10 | | 6n-3n= | | 5p+7q=45 | | -3(7v-2)+9v=-2(v+4) | | -19u=17-18u | | x-24=25 | | 3.2k=30 | | 31-4x=7(2n+2) | | -3(3x-2)=-3x+25 | | 2x+3(-7-4x)=14-5x | | -70x^2+36x=-10 | | -13-p=6p+1 | | -5(x+2)=x-2+2(2x+2) | | 3(n-15)+8=11 | | (H^2+4h-4)+(5h^2-8h+2)=6h^2-4h-2 | | 1/4+w=6 | | ax+6=(x+3) | | 2w+2l=l | | -16x^2+8x+190=0 | | 1/4+w=61/3 | | -6(x+2)-11=21+4 | | -3(y+5)=15 | | 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p | | 0.09xX=110.30 | | X+(x-1)=2(x+3) | | 12x-2m= | | 3x4/9= | | -5x+2(4x-15)=-63 | | -3(-7w+4)-3w=4(w-5)-4 |

Equations solver categories